Towards inclusive green growth: a holistic analysis of sustainable development goals in the agritourism sector of Jambi Province - Junaidi, Junaidi; Zulgani, Zulgani; Wahyudi, Ilham; Zevaya, Faradina (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2024)
This research aims to measure the extent of inclusive green growth in Jambi Province by considering the components of the Inclusive Green Growth Index that contribute to the potential of agrotourism and sustainable growth. It seeks to identify and analyze tourism potentials that can be leveraged to support inclusive green growth in various districts of Jambi Province. Additionally, the study aims to formulate strategies applicable to tourism villages in Jambi Province to realize agrotourism areas focused on improving the well-being of communities and the environment. This research employs both quantitative and descriptive qualitative methodologies. Data sources include primary and secondary data collected through interviews, observations, literature studies, and documentation. Informants were selected using purposive sampling, covering three regencies in Jambi Province: mountainous areas in Merangin Regency, non-mountainous and non-marine areas in Muaro Jambi Regency, and marine areas in Tanjung Jabung Timur Regency. The results indicate that Jambi Province has not yet achieved green inclusivity, with an Inclusive Green Growth Index value of 3.191. The study identifies several sample areas with green development potential, including Rantau Kermas Village in Merangin Regency, Tangkit Baru Village in Muaro Jambi Regency, and Kuala Simbur Village in Tanjung Jabung Timur Regency. Key findings include the green potential of tourism and plantations, dance arts, micro-hydropower plants (PLTMH), electricity, awards, funding, fishermen, locations, culinary, mangrove forests, customary forests, and marine products. Strategies to realize agrotourism areas based on improving community well-being and the environment include strengthening organizations, enhancing the quality of human resources, developing infrastructure, funding programs, applying customary law sustainability, offering tour packages, forming customary forest management groups, conducting research and development, implementing disaster mitigation measures, promoting tourism, and initiating the adopt-a-tree program.